Disponibilidade de crédito e desenvolvimento regional - França, Alex Luiz da Costa (2017)
The objective of this study is to analyze which factors influence the availability of credit to the Minas Gerais municipalities grouped in growth poles as well as the impact of the availability of credit for regional development. Against the background of Perroux's concept of accumulation/growth poles and being guided by the post-Keynesian view that money is not neutral and affects the regional economy, this research is justified by the scarcity of work on the factors that influence it availability of credit at the regional level, so as to be able to draw a comparison between the regions, in this case, divided into the accumulation poles of the state of Minas Gerais through its 66 microregions and 12 meso-regions. In this context, the research problem is synthesized in two questions: a) what factors influence the availability of credit for the Minas Gerais municipalities grouped in accumulation/growth poles? And, b) given these factors, what is the impact of the availability of credit for regional development in the period from 1999 to 2011? Seeking to elucidate the questions described, this dissertation adds two articles on credit and regional development to the empirical literature. In the first one, it is assumed that the distance from the studied municipality to its center of growth (hypercenter) has a negative effect on the amount of credit available, that the higher the preference for bank liquidity, the lower the availability of and that Gross Domestic Product (GDP), time deposits and population have a positive effect on the availability of credit, noting that the higher these factors, the greater the availability of credit. From regressions using the panel data technique, there is evidence that the distance is rather related to the available credit, but the effect is positive, showing that the greater the distance, the greater the credit available. The other hypotheses were confirmed for the Minas municipalities grouped in growth poles, given the positive relationship between the variables GDP, time deposits and population with the available credit and the negative relation between the preference for bank liquidity and credit. The second article, in a complementary manner and considering the question of the impact of credit on regional development, evaluated whether credit, representing financial development, has an impact on the variable GDP, used here as a representative of regional development, and concluded that credit has a positive and significant relationship at the 1% level with regional development. In all, the dissertation contributed to the inclusion of one more variable (distance) in the studies that relate credit and regional development, demonstrating that this is an important fact analysis besides showing that economic development has as one of its factors of influence credit, observing that the greater the credit available, the greater the development of a given region tends to be. The population analyzed in the two articles is made up of 853 municipalities in the state of Minas Gerais grouped in accumulation/growth poles (through their meso and microregions) with data referring to the availability of credit in the period from 1999 to 2011 available on the Central Bank's website (Bacen) and other information provided by the Institute of Applied Economic Research (Ipea), the Brazilian Institute of Geography and Statistics (IBGE).